2016
DOI: 10.1177/1359105316636949
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent cancer survivors’ posttraumatic stress symptoms: Concordance between self-report and maternal-proxy report

Abstract: Subsyndromal posttraumatic stress among pediatric cancer survivors has been associated with negative physical and mental health outcomes. However, adolescent self-report and mother-proxy report of adolescents' posttraumatic stress symptoms evidenced varying concordance depending on methodology. There was moderate concordance, particularly among younger respondents, when total posttraumatic stress symptoms were viewed continuously and low-moderate concordance when viewed categorically; moderate-strong concordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…This finding is contrary to earlier meta-analyses that only found low to moderate agreements between caregivers and their children and adolescents (Achenbach et al, 1987;Los Reyes et al, 2015). Nevertheless, some individual studies in children and adolescents with physical illnesses found similar results (Clawson et al, 2013;Erickson et al, 2017;Phipps et al, 2005;Stevanovic et al, 2012). One explanation could be that caregivers are more aware of their children's and adolescents' mental health concerns and actively seek treatment for them.…”
Section: Caregiver-reported Outcomescontrasting
confidence: 70%
See 1 more Smart Citation
“…This finding is contrary to earlier meta-analyses that only found low to moderate agreements between caregivers and their children and adolescents (Achenbach et al, 1987;Los Reyes et al, 2015). Nevertheless, some individual studies in children and adolescents with physical illnesses found similar results (Clawson et al, 2013;Erickson et al, 2017;Phipps et al, 2005;Stevanovic et al, 2012). One explanation could be that caregivers are more aware of their children's and adolescents' mental health concerns and actively seek treatment for them.…”
Section: Caregiver-reported Outcomescontrasting
confidence: 70%
“…In this sense, discrepancies are different yet valid information that can greatly assist diagnosis and treatment decisions. Interestingly, some studies from populations with physical illnesses such as cancer ( Clawson et al, 2013 ; Erickson et al, 2017 ; Phipps et al, 2005 ) and epilepsy ( Stevanovic et al, 2012 ) found significant moderate to high correlations between self-reported and caregiver-reported PTSS, depression and anxiety as well as no mean difference between raters. This contrary finding may be explained by a greater awareness and involvement of parents in their children’s health and treatment in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature has evaluated parent-child agreement and concordance for report of physical and psychological symptoms, as well as health-related quality of life. Varying degrees of disagreement and discordance have been demonstrated in the symptom reports of children with advanced cancer, children with cancer undergoing cancer treatment and adolescent cancer survivors and the reports of their parents (Baggott et al, 2014;Erickson et al, 2017;Zhukovsky et al, 2015). Inconsistency in parent-child agreement regarding perceived health-related quality of life in children with cancer has also been reported across studies, with some studies demonstrating high levels of concordance and others with low levels (Russell et al, 2006;Upton et al, 2008).…”
Section: Proxy Agreement and Concordancementioning
confidence: 99%
“…The WHO acknowledges each of these domains as equal contributors to one's conceptualization of their QOL and the well-being they derive from it. 3 While researchers in pediatric oncology have robustly explored the physical and psychological health domains of QOL, [4][5][6][7][8][9] the "social relations" domain has received less attention comparably. Our team previously evaluated commonly used patient-reported outcome measures (PROMs) and assessed the tools' abilities to accurately capture patients' subjective appraisals of QOL.…”
Section: Introductionmentioning
confidence: 99%